Impact of depatuxizumab mafodotin on health-related quality of life and neurological functioning in the phase II EORTC 1410/INTELLANCE 2 trial for EGFR-amplified recurrent glioblastoma. (April 2021) - Clement, Paul M.J.; Dirven, Linda; Eoli, Marica; Sepulveda-Sanchez, Juan M.; Walenkamp, Annemiek M.E.; Frenel, Jean S.; Franceschi, Enrico; Weller, Michael; Chinot, Olivier; De Vos, Filip Y.F.L.; Whenham, Nicolas; Sanghera, Paul; et al.
Abstract: Background: In the EORTC 1410/INTELLANCE 2 randomised, phase II study (NCT02343406), with the antibody–drug conjugate depatuxizumab mafodotin (Depatux-M, ABT-414) in patients with recurrent EGFR-amplified glioblastoma, the primary end-point (overall survival) was not met, and the drug had ocular dose-limiting toxicity. This study reports results from the prespecified health-related quality of life (HRQoL) and neurological deterioration-free survival (NDFS) exploratory analysis. Patients and methods: Patients (n = 260) were randomised 1:1:1 to receive either Depatux-M 1.25 mg/kg or 1.0 mg/kg intravenously every 2 weeks with oral temozolomide (TMZ) 150 mg/m 2, Depatux-M alone, or TMZ or oral lomustine (CCNU) 110 mg/m 2 (TMZ/CCNU). HRQoL outcomes were recorded using the EORTC core Quality of Life QLQ-C30, and brain cancer-specific QLQ-BN20 questionnaires. Questionnaires were completed at baseline, weeks 8 and 16, and month 6, and changes from baseline to each time point were calculated. NDFS was defined as time to first deterioration in World Health Organisation performance status. Results: Compliance with HRQoL was 88.1% at baseline and decreased to 37.9% at month 6. Differences from baseline between Depatux-M arms and TMZ/CCNU in global health/QoL status throughout treatment did not reach clinical relevance (≥10 points). Self-reported visual disorders deteriorated to a clinically relevant extent with Depatux-M arms versus TMZ/CCNU at all timepoints (mean differences range: 24.6–35.1 points). Changes from baseline for other HRQoL scales and NDFS were generally similar between treatment arms. Conclusions: Depatux-M had no impact on HRQoL and NDFS in patients with EGFR-amplified recurrent glioblastoma, except for more visual disorders, an expected side-effect of the study drug. Clinical trial registration: NCT02343406. Highlights: Clinically relevant increases in self-reported visual disorders with Depatux-M. Similar health-related quality of life scores between Depatux-M and standard care. Neurological deterioration-free survival was similar between treatments.